Ventilasi Mekanik pada Pasien Prolonged Acute Respiratory Failure Due to Ards and Dka; A Case Report - Nina Risnianingsih; Vera Susanti; Muhaemin Muhaemin; Ayu Prawesti Priambodo (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Prolonged acute respiratory failure is a very challenging critical medical condition, especially with comorbidities of Acute Respiratory Distress Syndrome (ARDS) and Diabetic Ketoacidosis (DKA). ARDS causes severe respiratory distress, while DKA in uncontrolled diabetes worsens metabolic and respiratory conditions. The complexity of managing prolonged respiratory failure lies in the need for intensive intervention, continuous monitoring, and careful adjustment of mechanical ventilation and multidisciplinary collaboration to achieve patient stability in the ICU. This report aims to describe the interventions given to patients with prolonged acute respiratory failure due to ARDS and DKA in the ICU of RSKK Bandung, and to explore the challenges in adjusting mechanical ventilation and managing these conditions. This study uses a descriptive approach by analyzing the case of a 37-year-old man who was admitted to the ICU with initial conditions of prolonged acute respiratory failure, ARDS, and Diabetic Ketoacidosis (DKA) characterized by shortness of breath, hypoxemia, and hyperglycemia. Data were collected through physical examination, laboratory results, blood gas analysis, and nursing interventions for respiratory and metabolic stabilization. Interventions provided included intensive monitoring, mechanical ventilation adjustment, blood glucose level regulation, and fluid and electrolyte balance monitoring. The patient experienced prolonged acute respiratory failure, which required mechanical ventilation with SIMV mode and pressure support, with dynamics of PEEP values given between 6-12 cmH2O. In addition, the patient showed high blood glucose levels (311 mg/dL) and ketonuria (+2), indicating DKA. Nursing interventions focused on adjusting mechanical ventilation (including SIMV and PEEP modes), regulating blood glucose through insulin drip, and monitoring fluids and electrolytes to reduce the risk of further complications. Management of patients with prolonged acute respiratory failure due to ARDS and DKA requires a very intensive and coordinated approach, including appropriate mechanical ventilation adjustments with special attention to SIMV mode and PEEP optimization and effective nursing interventions. This case highlights the uniqueness of managing prolonged acute respiratory failure, a challenge in ICU care, and the importance of team collaboration and the application of a personalized, evidence-based approach to critical care. Keywords: Nursing Interventions, Prolonged Acute Respiratory Failure, ARDS, Diabetic Ketoacidosis (DKA), Mechanical Ventilation.  ABSTRAK Prolonged acute respiratory failure merupakan kondisi medis kritis yang sangat menantang, terutama dengan komorbiditas Acute Respiratory Distress Syndrome (ARDS) dan Diabetic Ketoacidosis (DKA). ARDS menimbulkan gangguan pernapasan berat, sementara DKA pada diabetes tidak terkontrol memperburuk kondisi metabolik dan respirasi. Kompleksitas penanganan gagal napas yang memanjang terletak pada kebutuhan intervensi intensif, pemantauan berkelanjutan, serta penyesuaian ventilasi mekanik yang cermat dan kolaborasi multidisipliner demi mencapai stabilitas pasien di ICU. Laporan ini bertujuan untuk menggambarkan intervensi  yang diberikan kepada pasien dengan gagal napas akut yang memanjang akibat ARDS dan DKA di ruang ICU RSKK Bandung, serta untuk mengeksplorasi tantangan dalam penyesuaian ventilasi mekanik dan pengelolaan kondisi tersebut. Penelitian ini menggunakan pendekatan deskriptif dengan menganalisis kasus seorang pria berusia 37 tahun yang dirawat di ruang ICU dengan kondisi awal gagal napas akut yang memanjang, ARDS, dan Diabetic Ketoacidosis (DKA) yang ditandai dengan sesak napas, hipoksemia, dan hiperglikemia. Data dikumpulkan melalui pemeriksaan fisik, hasil laboratorium, analisis gas darah, serta intervensi keperawatan untuk stabilisasi pernapasan dan metabolisme. Intervensi yang diberikan meliputi pemantauan intensif, penyesuaian ventilasi mekanik, pengaturan kadar glukosa darah, dan pemantauan keseimbangan cairan serta elektrolit. Pasien mengalami gagal napas akut yang memanjang, yang memerlukan ventilasi mekanik dengan mode SIMV dan pressure support, dengan dinamika nilai PEEP yang diberikan antara 6-12 cmH2O. Selain itu, pasien menunjukkan kadar glukosa darah yang tinggi (311 mg/dL) dan ketonuria (+2), menandakan adanya DKA. Intervensi keperawatan difokuskan pada penyesuaian ventilasi mekanik (termasuk mode SIMV dan PEEP), pengaturan glukosa darah melalui insulin drip, serta pemantauan cairan dan elektrolit untuk mengurangi risiko komplikasi lebih lanjut. Penanganan pasien dengan gagal napas akut yang memanjang akibat ARDS dan DKA memerlukan pendekatan yang sangat intensif dan terkoordinasi, termasuk penyesuaian ventilasi mekanik yang tepat dengan perhatian khusus pada mode SIMV dan optimasi PEEP serta intervensi keperawatan yang efektif. Kasus ini menyoroti keunikan dalam mengelola kondisi gagal napas akut yang memanjang, yang menjadi tantangan dalam perawatan ICU, dan pentingnya kolaborasi tim medis serta penerapan pendekatan yang personal dan berbasis bukti dalam perawatan pasien kritis. Kata Kunci: Intervensi Keperawatan, Gagal Nafas Akut yang Memanjang, ARDS, Ketoasidosis Diabetikum (KAD), Ventilasi Mekanik.